Lemma 57.87.8. Let $f : X \to Y$ and $g : Y \to Z$ be proper morphisms of schemes. Assume

1. cohomology commutes with base change for $f$, and

2. cohomology commutes with base change for $g$.

Then cohomology commutes with base change for $g \circ f$.

Proof. We will use the equivalence of Lemma 57.87.6 without further mention. Let $\ell$ be a prime number. Let $\mathcal{I}$ be an injective sheaf of $\mathbf{Z}/\ell \mathbf{Z}$-modules on $X_{\acute{e}tale}$. Then $f_*\mathcal{I}$ is an injective sheaf of $\mathbf{Z}/\ell \mathbf{Z}$-modules on $Y_{\acute{e}tale}$ (Cohomology on Sites, Lemma 21.14.2). The result follows formally from this, but we will also spell it out.

Let $Z' \to Z$ be a morphism of schemes and set $Y' = Z' \times _ Z Y$ and $X' = Z' \times _ Z X = Y' \times _ Y X$. Denote $a : X' \to X$, $b : Y' \to Y$, and $c : Z' \to Z$ the projections. Similarly for $f' : X' \to Y'$ and $g' : Y' \to Z'$. By Lemma 57.87.5 we have $b^{-1}f_*\mathcal{I} = f'_*a^{-1}\mathcal{I}$. On the other hand, we know that $R^ qf'_*a^{-1}\mathcal{I}$ and $R^ q(g')_*b^{-1}f_*\mathcal{I}$ are zero for $q > 0$. Using the spectral sequence (Cohomology on Sites, Lemma 21.14.7)

$R^ pg'_* R^ qf'_* a^{-1}\mathcal{I} \Rightarrow R^{p + q}(g' \circ f')_* a^{-1}\mathcal{I}$

we conclude that $R^ p(g' \circ f')_*a^{-1}\mathcal{I} = 0$ for $p > 0$ as desired. $\square$

Comment #3213 by Alexander Schmidt on

In the statement of the Lemma, $f\circ g$ should be replaced by $g\circ f$.

There are also:

• 4 comment(s) on Section 57.87: The proper base change theorem

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).